EDUKASI PERNIKAHAN DINI UNTUK MEWUJUDKAN KELUARGA DAN MASYARAKAT TANGGUH DI DESA BANYUANYAR KECAMATAN KALIBARU - Benny Angga`` Permadi; Eka Ramiati; Rengga Alfani; Nur Azizah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aimed to provide knowledge and understanding especially in our society in general about the dangers early marriages. A method of devotion is socialization through training Types of data collected is data primary and secondary. From the observation, early show that one of the factors that promote a early marriages among them fraternization so that the occurrence of pregnant out of wedlock. From early marriages does induce the impact of that is less prepared mentally, easy when the divorce, violence in the household, and also of economic factors.